Accented America the cultural politics of multilingual modernism - Miller, Joshua (Joshua L.) (New York ; Oxford : Oxford University Press, 2011)
This text is a sweeping study of US literature between 1890-1950 that reveals a long history of English-only nationalism: the political claim that US citizens must speak a nationally distinctive form of English.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: American literature -- 20th century -- History and criticism; National characteristics, American, in literature; Modernism (Literature) -- United States; Multilingualism and literature; Americanisms in literature